Balanced nutrition education as an effort to prevent stunting in toddlers - Dahniar; Arisna Kadir (Abdimas Polsaka, 2025)
Nutritional problems in toddlers, including stunting, wasting, and overweight, remain a primary global health concern. Stunting is closely linked to specific deficiencies in vitamins and minerals, influenced by factors such as maternal education, family income, maternal knowledge of nutrition, breastfeeding practices, complementary feeding age, micronutrient adequacy, infection history, and genetics. This community service program aimed to increase maternal knowledge of balanced nutrition to prevent toddler stunting. The activity was conducted on January 20, 2025, at the Posyandu in the Pattingalloang Community Health Center working area, involving 20 participants, supported by lecturers, students, midwives, and local health cadres. Educational interventions were delivered through lectures, discussions, and Q&A sessions. Pre-test results showed that 65% of participants had good knowledge and 35% had poor knowledge regarding balanced nutrition and stunting prevention. Post-test results showed improvement, with 80% demonstrating good knowledge and only 20% remaining in the poor category. The findings highlight that targeted nutrition education can significantly improve maternal understanding and awareness, possibly reducing stunting prevalence. Follow-up programs and home-based health services were also recommended to sustain knowledge and improve child health outcomes